ANALISIS YURIDIS TERHADAP ASAS PEMBENTUKAN DAN ASAS MATERI PERATURAN WALIKOTA AMBON TENTANG PEMBATASAN SOSIAL BERSKALA BESAR - Lekipiouw, Sherlock. H.; Salmo, Hendrik; Mustamu, Julista; M. Y. Tita, Heillen. (UNES Law Review, 2021)
There are several articles in the Ambon Mayor's Regulation Regarding PSSB which do not reflect the formation and regulations of the legislation. The purpose of this research is to study and analyze the implementation as the formation and principle of the material of legislation. The research method used is normative legal research. The results of the study show that the establishment of Ambon Mayor Regulation Number 18 of 2020 concerning the Implementation of Large-Scale Social Restrictions in Handling Corona Virus Disease 2019 (COVID-19) in Ambon City has not reflected as a statutory regulation and the material principle of statutory regulations.